PROMOTING READING ENGAGEMENT: THE SCHOOL LITERACY MOVEMENT AT JUNIOR HIGH SCHOOL 1 SEBATIK - Ridwan, Ridwan; Pamuji, Siti Sulistyani; Apriani, Eva (University of Kuningan, 2023)
This study aims to analyze the indicators in the process of implementing the school literacy movement at junior high school 1 Sebatik and the obstacles faced. The research method used in this research is descriptive qualitative method. The data collection techniques used are observation, interviews and documentation. The results of this study describe that there are six indicators in the process of implementing the literacy movement at at junior high school 1 Sebatik, namely reading activities for 15 minutes, journaling literacy results, increasing interesting reading books, making literacy corners, conducting competitions that support the school literacy movement and making interesting libraries in support the school literacy movement. In addition, it was found that there were four obstacles experienced by at junior high school 1 Sebatik in the process of the school literacy movement, including: teachers have difficulty in carrying out literacy more than 15 minutes before class, teachers have difficulty providing digital books in class, teachers have difficulty in carrying out activities to respond to reading books, and teachers have difficulty in carrying out creative writing activities.